Karakteristik Atenuasi Gelombang Seismik di Daerah Ternate, Maluku Utara dengan menggunakan Analisis Gelombang Coda - Satriani, Fatima Marjan Keshia; Anggono, Titi; Hasanah, Mia Uswatun (Jurnal Geofisika, 2025)
The convergence of the Philippine Plate, the Eurasian Plate, the Australian Plate, and the double subduction between the Molucca Sea Plate, the Sangihe Through, and the Halmahera Through have created a complex tectonic setting in North Maluku. Due to intense tectonic activity, this region frequently experiences the possibility of tectonic events like earthquakes. In the attenuation seismology approach, seismic waves propagating below the surface are measured for amplitude amplification and attenuation. Seismic wave attenuation propagating in this region is described using the coda attenuation method on coda seismic waves. In order to determine the degree of tectonic activity in the Ternate region, 129 earthquake data points from four sites in North Maluku that were less than 40 kilometers deep were processed. Stations SP01 and SP02 are situated on Ternate Island, whereas stations BB06 and SP28 are situated on Hiri Island. A sampling frequency of 2 – 10 Hz and a window length of 20 – 120 s were used to get values of the coda (Q0), η, Qc, and attenuation (Qc-1). Twi times the S-wave’s arrival time is assumed for the coda wave. The coda variation values (Q0) were recorded as follows: an average of 112. 167 for station SP01, 91.071 for station SP02, 116.089 for station SP28, and 112.843 for station BB06. The value increases and decreases within the 20 – 40 s range. The values of attenuation and (Q0) are inversely related. The Q0 and Qc values obtained are low due to the high damping value in the Ternate area. The high damping (Qc-1), high eta (η) value (>1), and low Q0 value (<200) are thought to be signs of strong tectonic activity in the Ternate, Halmahera, North Maluku region.